Common Principles of European Intellectual Property Law - Ohly, Ansgar (Mohr Siebeck, 2012)
Intellectual property law has been harmonized by EU law to a considerable extent. At the same time intellectual property rights have converged. The academic discussion has not kept pace with this development. European intellectual property law is often seen through the spectacles of national law; pan-European discussions about issues of Community law seem to be the exception rather than the rule. The contributors to this volume investigate if and to what extent European rules and principles applicable to all intellectual property rights already exist or whether they can be found on the basis of the acquis communautaire and comparative law. In particular, they discuss the merits and the methodology of common principles before turning to several areas of substantive intellectual property law such as grounds of protection, secondary liability and exceptions, to enforcement and finally to the relationship between intellectual property and neighbouring areas of EU law.